How well designed is your servicescape?. Issue 3 (21st March 2022) - Nair, K. Unnikrishnan; Kumar, Deepak S.; Purani, Keyoor
Abstract : Purpose: Through empirical research anchored in environmental psychology, the paper presents formative indicators that form an evaluation set "S.E.E." (service environment evaluation), to simplify and systematize the measurement of visual aesthetics of servicescapes through consumers' perspective. Design/methodology/approach: The authors adopted formative index development methodology, employing a one-shot experimental design using photographic surrogates of four different servicescapes ( n = 1400), and testing the index with eight noted global servicescape images. Findings: Findings reveal that visual aesthetics of servicescapes can be captured using the composite index we developed with five dimensions: complexity, coherence, legibility, mystery and novelty. Also, service type: hedonic/utilitarian, does influence how consumers evaluate servicescape visual appeal. Originality/value: Formative indicators constituting S.E.E. enables assessment of subjective visual aesthetics of servicescapes holistic, objective and an effortless task for marketers, designers and decision-makers; and helps them reliably decide on and skillfully design servicescapes with the required visual appeal.